Agricultural socialized services in China’s smallholder farming systems: a systematic review of service types, benefits, and measurement challenges - Rong Zeng; Meseret C. Abate; Cai Baozhong; Amsalu K. Addis; Xiangyun Yi; Shaoping Jiang; Xu Yan; Betelhem A. Geremew; Amsalu N. Alamerew; Amsalu N. Alamerew (Frontiers in Agronomy)
This review investigates the existing research on agricultural socialized services (ASS), focusing on their benefits to smallholder farmers and the barriers these farmers encounter in accessing such services. ASS are vital to modern agricultural systems, influencing both service providers and smallholder practices in various national contexts. Although previous studies have examined trends and levels of ASS development, there has been limited exploration of the specific types of services that warrant further research and the obstacles facing smallholders in their implementation. This deficiency in information heightens the vulnerability of smallholder farmers to ongoing and unpredictable risks. To address this issue, we employed a modified Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique to conduct a thorough literature search, applying eligibility criteria to identify pertinent studies. The selected literature was categorized by service type and their reported benefits to smallholders, without imposing restrictions on study methodologies. Our findings indicate that 66% of the analyzed studies concentrated on production-stage services, particularly machinery outsourcing, which is largely influenced by rural labor migration and aims to optimize yields. In contrast, only 16% of the studies explored multi-stage ASS integration (which includes pre-production, production, and post-production services), and none examined the concept of holistic service bundling. While mechanization services emerged as prominent due to their measurable productivity enhancements, significant gaps remain in assessing intangible benefits and understanding systemic trade-offs. Throughout the review, we identified challenges in measuring the effects of these services, such as difficulties in quantifying subjective impacts, data validation shortcomings, and the need for improved simulation models. Ultimately, this review calls for a shift in research direction towards a wider array of service types, the development of cost-effective delivery mechanisms, and strategies to improve access, all of which are essential to enhancing the resilience and livelihoods of smallholder farmers.